DH2020 Book of Abstracts - Crompton, Constance; Estill, Laura; Guiliano, Jennifer (Université d'Ottawa | University of Ottawa, 2020)
The DH2020 Book of Abstracts is an important contribution to the field of digital humanities as it captures the presentations at the annual international conference hosted by the Alliance for Digital Humanities Organization. At 598 pages long, this volume brings together 475 abstracts for paper presentations, panels, posters, lightning talks, and workshops. The contents showcase the work of authors from five continents, highlighting the latest in all areas of digital humanities research, including history, GLAM (galleries, libraries, archives, and museums), literature, art, linguistics, digital pedagogy, geospatial information systems, and more. The DH2020 conference was slated to be held at the University of Ottawa and Carleton University in July 2020, but was cancelled in March due to the covid pandemic. The abstract texts are available under Creative Commons licence CC-BY-4.0.
Keywords: Digital Humanities; Conference abstracts; Ottawa DH2020